2000
DOI: 10.1007/s002130000410
|View full text |Cite
|
Sign up to set email alerts
|

The 5-HT 3 agent N -(3-chlorophenyl)guanidine (MD-354) serves as a discriminative stimulus in rats and displays partial agonist character in a shrew emesis assay

Abstract: Taken together, the results indicate that MD-354 is a 5-HT3 agonist and that it might be an agent with partial agonist activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Chloroguanidine was previously studied as a possible antimalarial drug and was found to have acute toxicity and reproductive effects in various animal models (22). While the breakdown product that we have identified is para-substituted, the meta-substituted version of chlorophenylguanidine ( N -(3-Chlorophenyl)guanidine) is a 5-HT 3 receptor agonist, and is able to cross the blood brain barrier (23). 5-HT 3 receptor agonists were being examined for the treatment of abuse of various stimulants and emesis from chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Chloroguanidine was previously studied as a possible antimalarial drug and was found to have acute toxicity and reproductive effects in various animal models (22). While the breakdown product that we have identified is para-substituted, the meta-substituted version of chlorophenylguanidine ( N -(3-Chlorophenyl)guanidine) is a 5-HT 3 receptor agonist, and is able to cross the blood brain barrier (23). 5-HT 3 receptor agonists were being examined for the treatment of abuse of various stimulants and emesis from chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…A compound that reduces drug discrimination would be a candidate for the treatment of ethanol and/or drug abuse [185]. Although one study found that 5-HT3 agonists and antagonists appear to have no discriminative stimulus properties [186], an earlier study [187] reported that the partial 5-HT3 agonist meta-chlorophenylguanidine (MD-354) has discriminative stimulus properties that generalized to quipazine (ED50=0.2 mg/kg), m-CPBG, ED50=1.4 mg/kg), 2-methyl 5-HT (ED50=4.5 mg/kg), 1-(2-naphthyl)biguanide (2-NBG, ED50=1.9 mg/kg), and N-(2-naphthyl)guanidine (2-NG, ED50=0.7 mg/kg). Moreover, these stimulus properties of MD-354 were attenuated by the administration of either zacopride or tropisetron [187].…”
Section: 5-ht3 Receptors In Animal Models Of Addictionmentioning
confidence: 99%
“…In this respect, the present results are consistent with findings with other behavioural paradigms. Although quipazine has been found to behave like other 5-HT 3 receptor agonists including m-CPBG, in some tests (Dukat et al 2000), many of its behavioural effects, including the induction of head twitching (Sanchez and Arnt 2000) and lordosis (Wolf et al 1998), and the enhancement of progressive ratio schedule performance (Wolff and Leander 2000), are believed to be mediated by 5-HT 2 receptors. In drug discrimination studies, quipazine can substitute for both 5-HT 3 (Dukat et al 2000) and 5-HT 2A (Wolff and Leander 2000;Smith et al 2002) receptor agonists.…”
Section: Treatmentmentioning
confidence: 98%
“…In doses similar to those used here, m-CPBG has been found to be active in behavioural tests of anxiety, showing an anxiogenic profile in the elevated plus maze test (Andrews and File 1992) and reversing the effect of the 5-HT 3 receptor antagonists ICS 205-930 (Nakagawa et al 1998) and ondansetron (Eguchi et al 2001) in other anxiety models. In the same dose range, m-CPBG fully substitutes for other 5-HT 3 receptor agonists in drug discrimination tests (Dukat et al 2000). m-CPBG (1 and 10 mg kg −1 ) has been found to disrupt the acquisition of conditioned responses in an autoshaping paradigm, an effect that was completely reversed by coadministration of the 5-HT 3 receptor antagonists ondansetron and tropisetron (Hong and Meneses 1996).…”
Section: Treatmentmentioning
confidence: 98%